Activation of the MET receptor attenuates doxorubicin‐induced cardiotoxicity in vivo and in vitro. (29th May 2020) - Gallo, Simona; Spilinga, Martina; Albano, Raffaella; Ferrauto, Giuseppe; Di Gregorio, Enza; Casanova, Elena; Balmativola, Davide; Bonzano, Alessandro; Boccaccio, Carla; Sapino, Anna; Comoglio, Paolo Maria; Crepaldi, Tiziana
Abstract : Background and Purpose: Doxorubicin anti‐cancer therapy is associated with cardiotoxicity, resulting from DNA damage response (DDR). Hepatocyte growth factor (HGF) protects cardiomyocytes from injury, but its effective use is compromised by low biodistribution. In this study, we have investigated whether the activation of the HGF receptor—encoded by the Met gene—by an agonist monoclonal antibody (mAb) could protect against doxorubicin‐induced cardiotoxicity. Experimental Approach: The mAb (5 mg·kg −1 ) was injected in vivo into C57BL/6J mice, before doxorubicin (three doses of 7 mg·kg −1 ). Cardiac functions were evaluated through MRI after treatment termination. Heart histological staining and mRNA levels of genes associated with heart failure ( Acta1 and Nppa ), inflammation ( IL‐6 ), and fibrosis ( Ctgf, Col1a2, Timp1, and Mmp9 ) were assessed. MAb (100 nM) was administered in vitro to H9c2 cardiomyoblasts before addition of doxorubicin (25 μM). DDR and apoptosis markers were evaluated by quantitative western blotting, flow cytometry, and immunofluorescence. Stattic was used for pharmacological inactivation of STAT3. Key Results: In vivo, administration of the mAb alleviated doxorubicin‐induced cardiac dysfunction and fibrosis. In vitro, mAb mimicked the response to HGF by (a) inhibiting histone H2AX phosphorylation at S139, (b) quenching the expression of the DNA repair enzyme PARP1, and (c) reducing the proteolytic activation of caspase 3. The MET‐driven cardioprotection involved, at least in vitro, the phosphorylation of STAT3. Conclusion and Implications: The MET agonist mAb provides a new tool for cardioprotection against anthracycline cardiotoxicity.